Tilemann Heßhusius - Wilkens, Cornelius August,Heshusen, Tilemann (Breitkopf und Härtel, 1860)
Goslar und Rostock. - S. 25-39
Keywords: Biografie; Heshusius; Tilemann; 1527-1588; Doctrines; Theology; Doctrinal